Effect of 5-day dry immersion on the human foot morphology evaluated by computer plantography and soft tissues stiffness measuring - Saveko, Alina (Sci Rep, 2021)
16 participants have been subjected to Dry Immersion model (DI) for 5 days. DI reproduces the space flight factors such as lack of support, mechanical and axial unloading, physical inactivity, elimination of vertical vascular gradient. Long-term bed rest is also associated with similar factors, so the results of the study may be useful for clinical medicine. Computer plantography and measuring the stiffness of the soft tissues of the foot and superficial muscles of the shin (mm. tibialis anterior and peroneus longus) were performed twice before DI exposure, on the 2nd and 4th days of DI exposure, as well as on the 2nd day of the recovery period. DI exposure effects the parameters under study in two ways: by raising the longitudinal arch and by flattening the transverse arch, which is accompanied by a decrease in the soft tissues stiffness of the foot and superficial muscles of the shin. The work reveals the phenomenon of compensating the longitudinal arch state by changing the characteristics that reflect the transverse arch state. The results of the study for the first time demonstrate the correlation of the foot morphological characteristics with a decrease in stiffness of mm. peroneus longus and tibialis anterior.